Dairy Innovation Portal: A web-based platform to address the Farmer-led Innovations in the Indian Dairy Sector - Kar, Priyajoy; H.R. Meena; K.S.Kadian; B.S.Meena; Gopal Sankhala; A.K.Singh; RAKESH KUMAR; PAWAN SINGH; Amitava Panja; Neela Madhav Patnaik; Saikat Maji; Ph. Romen Sharma (Indian Journal of Dairy Science, 2024)
The study was carried out in four districts of Haryana and Punjab state to conduct the baseline survey about developing a Dairy Innovation portal for the dairy stakeholders. A first of its kind Dairy Innovation Portal was developed consisting the details of Farmer- led Innovations resulted from the preliminary survey. The portal was developed keeping in view the diverse needs of the stakeholders in the dairying sector. The multilingual portal was equipped with innovation submission forms in farmers native language for easy access. The portal also directs the farmers to claim Intellectual Property benefits from the government organizations. A central database for documentation of farmer-led innovations in dairying will make it simple for people who want to access it and beneficial for dissemination. Futuristic vision enables this portal to cover farmer-led innovation in pan-India exploration which can bring upon a radical change in the Indian Dairy Sector.